2017
DOI: 10.1007/s40615-017-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Challenges in the Post-Affordable Care Act (ACA) Era: a Qualitative Study of the Perspective of Low-Income People of Color in Metropolitan Detroit

Abstract: Low-income people of color are at risk of remaining uninsured due to a variety of factors. This study examined Affordable Care Act (ACA)-related and other health insurance enrollment experiences, observations, navigation needs, and experiences maintaining health insurance coverage among low-income communities of color in an economically disadvantaged community (Metropolitan Detroit). We conducted nine focus groups (n = 87) between May and June 2015. Participants were recruited through community-based organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The content and focus of Insuring Good Health were informed by focus groups conducted with key racial/ethnic populations in Detroit: African American, Latino/Hispanic, and Arab American or Middle Eastern groups (Patel, Jensen, et al, 2018). Key themes concluded that although health insurance is perceived as important, confusion and frustration persist around health plan benefits and coverage, eligibility requirements and key provisions of the ACA, and enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content and focus of Insuring Good Health were informed by focus groups conducted with key racial/ethnic populations in Detroit: African American, Latino/Hispanic, and Arab American or Middle Eastern groups (Patel, Jensen, et al, 2018). Key themes concluded that although health insurance is perceived as important, confusion and frustration persist around health plan benefits and coverage, eligibility requirements and key provisions of the ACA, and enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Even 5 years after the passage of the ACA, there were high reports of knowing nothing or very little about the ACA, and lacking basic knowledge with health insurance plan terminology, differences in features across plans, and maintaining health insurance. These trends are particularly heightened among racial/ethnic communities (Ali, Combs, Muvuka, & Ayangeakaa, 2018; Ghaddar, Byun, & Krishnaswami, 2018; Loewenstein et al, 2013; Patel, Jensen, et al, 2018; Politi et al, 2014).…”
mentioning
confidence: 99%
“…As a result, many patients who are eligible for public programs are not aware, and therefore are not registered. 37 , 46 , 47 The application process is often difficult to navigate, and families may experience logistical barriers such as lack of financial resources and transportation. Health literacy challenges also affect ability to access care.…”
Section: Presenting To the Emergency Departmentmentioning
confidence: 99%
“… 51 , 52 Likewise, restrictive policies, statements, and attitudes towards immigrant families coming from the Trump administration also undoubtedly affect families' comfort level with seeking medical care 53 and willingness to trust the health care system with their personal information. 46 Most recently, the amended Public Charge rule caused confusion and fear among immigrant families, leading to decreased utilization of healthcare, even by those not directly affected by the rule change. 19 , 38 , 54.…”
Section: Presenting To the Emergency Departmentmentioning
confidence: 99%
“…Thirty-nine states including the District of Columbia (D.C.) have expanded Medicaid while 12 states have not expanded [ 3 ], thus putting many low-income nonelderly adults at risk of remaining uninsured [ 4 ]. Purchasing private insurance from the newly established marketplace was an option for nonelderly adults unable to get Medicaid, but some found it unaffordable even with the possibility of receiving federal subsidies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%